Gene characterization and expression of the γδ T cell co-receptor WC1 in sheep. (March 2021) - Gillespie, Alexandria; Yirsaw, Al; Kim, Sookyung; Wilson, Katherine; McLaughlin, Julie; Madigan, Mackenzie; Loonie, Kathleen; Britton, Emily; Zhang, Fengqiu; Damani-Yokota, Payal; Gunasekaran, Karthick P.; Telfer, Janice; et al.
Abstract: Sheep are known to express the hybrid co-receptor/pattern recognition receptor WC1 on their γδ T cells but details of the ovine WC1 multigenic array and gene expression were unknown. Annotation of the sheep genome assembly (Oar_rambouillet_v1.0) yielded 15 complete and 42 partial WC1 genes predicted to code for six different protein structures. RT-PCR amplification of the most distal scavenger receptor cysteine rich (SRCR) domain known as a1, which serves as the gene signature, from genomic and cDNA templates verified the majority of annotated genes. As for cattle and goats, sheep a1 domain sequences included WC1.1 and WC1.2 types. A unique ovine gene, WC1-16, had multiple SRCR a-pattern domains in tandem similar to one found in goats. Intracytoplasmic domains of WC1 transcripts had splice variants that may affect signal transduction. The larger number of WC1 genes in sheep and differences in structures and splice variants relative to cattle could have implications in expression patterns and engagement of γδ T cells by pathogens or vaccine constructs. Highlights: 15 complete WC1 genes were found on ovine chromosome 3. 42 partial WC1 genes were also found on ovine chromosome 3. Transcripts for intracytoplasmic domains had multiple splice variants. 6 different WC1 gene structures were found. 5 subpopulations of γδ T cells were described.